What makes a church sacred? : legal and ritual perspectives from late antiquity - Farag, Mary, 1985- (Transformation of the classical heritage ;, 2021)
"If churches belong to no one, what is their purpose? Mary K. Farag persuasively demonstrates that three interest groups cared about this question in late antiquity: law-makers, Christian leaders, and wealthy lay-persons. Most of the time, their answers co-existed, sitting side-by-side like tectonic plates. Yet the plates did not always sit still, and it is events on their colliding boundaries that account for familiar Christian controversies in novel ways. What Makes a Church Sacred? argues that scholarship misunderstands well-known religious figures by ignoring the legal issues they faced. In this seminal text, Farag nuances the scholarly conversations on sacred space, gift-giving, wealth, and poverty in the late antique Mediterranean world, making use not only of Latin and Greek sources, but also Coptic and Arabic evidence"--